KONTRIBUSI SARANA PRASARANA DAN MOTIVASI BELAJAR SISWA TERHADAP HASIL BELAJAR MATA DIKLAT DASAR LISTRIK DAN ELEKTRONIKA KELAS X DAN XI AUDIO VIDEO DI SMK NEGERI 1 SUMATERA BARAT - Sahrul Efendi Ray; Almasri Almasri; Delsina Faiza (Universitas Negeri Padang, 2018)
The purpose of research to reveal how much contribution of infrastructure and learning motivation of students together or individually to the learning outcomes. The research population is 60 people and the sample is 38 students of class X and XI TAV in SMK Negeri 1 West Sumatera. The sampling technique was done randomly (Simple Random Sampling). Data on student learning outcomes is obtained from basic teachers of electrical and electronics training. While the data facilities and learning motivation of students are collected through questionnaires distributed to students by using Likert scale that has been tested the validity and reliability. The result of data analysis shows that (1) the learning facilities and motivation of student learning together contribute significantly to the learning outcomes of students of class X and XI TAV SMK Negeri 1 West Sumatera of 39.40%, (2) infrastructure facilities contribute significantly to the result of study of student of class X and XI TAV SMK Negeri 1 West Sumatera equal to 25,97%, (3) student learning motivation contribute significantly to result of student learning class X and XI TAV SMK Negeri 1 West Sumatera equal to 16,20%.Keywords: contribution of infrastructure, learning motivation, simple random sampling.